NON-LINEAR OPTIMIZATION FOR GAS TRANSMISSION PIPELINE NETWORK USING HEURISTIC - KETUT OSCAR EDY (NIM: 12299047), I
The development of gas transmission pipeline network consumes a huge cost. The costs consist of the investment cost and operation cost. Hence, it is important to do optimization to obtain total minimum cost but still fulfills the conditions. This final project studies a problem of optimization for large gas transmission pipeline network that connects some set of sources, compressors, and consumers with parallel and serial network. The parameters being optimized here are the diameters of the pipeline in each segment, whereas the objective function is to minimize the total cost. The corresponding constraints consist of maximum pressure in each pipe (Pmax) and pipeline flow equation of Panhandle A and Panhandle B. The real optimum is not too important to obtain in practice. Instead, it is sufficient to obtain solutions that are close the optimum. Considering only discrete values of diameter size, which are available in the market, the problem reduces to a discrete constraint optimization problem. This final project presents heuristic algorithm that gives fast computation for finding near optimum solutions for large pipeline network. This final project also discusses about model development in determination of toll fee.